PENGARUH KOMPENSASI, LOYALITAS KARYAWAN, DAN LINGKUNGAN KERJA TERHADAP KINERJA MELALUI PRODUKTIVITAS KARYAWAN SEBAGAI VARIABEL INTERVENING DI J&T CARGO BESUKI - Subro Wahyu Nurcahyo; Ediyanto Ediyanto; Riska Ayu Pramesthi (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Human resources (HR) are essential assets that significantly influence organizational success. This research seeks to examine how compensation, employee loyalty, and the work environment affect employee performance, both directly and indirectly through the mediating role of employee productivity. The study was carried out at J&T Cargo Besuki utilizing a quantitative research method. Data were gathered through surveys using questionnaires distributed to 30 participants, selected using a total sampling technique, which included the entire population. Data analysis and hypothesis testing were conducted using the Partial Least Squares (PLS) approach with the aid of SmartPLS 3.0 software. The findings demonstrate that compensation has a positive but statistically insignificant impact on employee performance. Similarly, employee loyalty shows a positive yet non-significant effect. In contrast, the work environment has a significant and positive influence on performance. In terms of productivity, both compensation and employee loyalty contribute positively but not significantly, whereas the work environment has a meaningful positive effect. Furthermore, employee productivity itself exerts a positive but statistically insignificant influence on performance. The indirect effects of compensation, loyalty, and the work environment on performance—mediated by productivity—are positive, though not statistically significant. These results indicate that while compensation and loyalty play supportive roles, they may not effectively enhance performance without a favorable work environment. Among the variables examined, the work environment is identified as the most impactful factor in boosting both productivity and employee performance. This research underscores the critical need for a positive and supportive workplace atmosphere to optimize employee effectiveness and organizational outcomes.